Surgical treatment of spinal deformities in Duchenne muscular dystrophy: a long term follow-up study - Cervellati, S. (Springer-Verlag, 2004)
BACKGROUND: Surgical treatment of spinal deformities in Duchenne muscular dystrophy (DMD) is influenced by a number of factors which have proven to be a difficult challenge. Each case should be carefully evaluated, considering not only the natural history of the spinal deformity, but also the patient’s general condition. These should be thoroughly assessed through clinical and radiographic investigations together with other medical specialists. Life expectancy should be determined according to the cardio-respiratory function, and both preoperative and postoperative quality of life should be taken into consideration, trying to imagine the functional status of each patient after surgery. METHODS: From February 1985 to February 2000, 58 patients with spinal deformity in DMD were surgically treated. Of 25 patients that were operated on between 1985 and 1995, only 20 were followed-up after 5 years because 5 of them had died during this time. Therefore, the present study focuses on the results obtained in 20 cases. The 20 cases reviewed presented with a mean angular value of scoliosis equal to 48° (range 10–92°). Spinal fusion with our modified Luque technique [6] was performed in 19 cases, whereas CD instrumentation was applied in only one case. RESULTS: At the 5 year follow-up (range 5.6–10 years), the age ranged from 18 to 24 years and averaged 20.4 years. The postoperative angular value of scoliosis averaged 22° (58%, range 0–43°), the mean correction at follow-up was 28° (range 0–60°), and the mean loss of correction was equal to 6° (range, 0–11°). Vital capacity showed a slow progression, slightly inferior to its natural evolution in untreated patients. The severest complication was the death that occurred in one of the patients. CONCLUSIONS: According to the present study, an early surgery (angular value lower than 35–40°) dramatically reduces the rate of risk factors associated with spinal deformities in DMD, and its advantages far exceed the disadvantages, above all in terms of quality of life.